2021
DOI: 10.1097/iae.0000000000003137
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Retinal Explants as a Source of Retinal Progenitor Cells

Abstract: Supplemental Digital Content is Available in the Text. There is sustained and growing interest in the use of stem cells and retinal progenitor cells as a possible treatment for retinal dystrophy and degeneration. In this article, we provide the first description of spontaneously migrating progenitor cells from living human donor surgical retinal explants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The surgical or cadaveric retinal tissue was transferred immediately into a tissue culture insert containing 300 μL of pre-warmed neurobasal A media supplemented with 2% B27 supplement, 1% N2 supplement, 0.8 mM L-glutamine, 100 units/mL penicillin and 100 μg/mL streptomycin. The culture insert was subsequently placed within a well of a 24-well cell culture plate containing 400 μL of supplemented neurobasal A media 47 . The tissue was exposed or unexposed to the CamkIIα-bReachES-TS-eYFP treatment vector before www.nature.com/scientificreports/ incubation.…”
Section: Human Retinal Explantsmentioning
confidence: 99%
“…The surgical or cadaveric retinal tissue was transferred immediately into a tissue culture insert containing 300 μL of pre-warmed neurobasal A media supplemented with 2% B27 supplement, 1% N2 supplement, 0.8 mM L-glutamine, 100 units/mL penicillin and 100 μg/mL streptomycin. The culture insert was subsequently placed within a well of a 24-well cell culture plate containing 400 μL of supplemented neurobasal A media 47 . The tissue was exposed or unexposed to the CamkIIα-bReachES-TS-eYFP treatment vector before www.nature.com/scientificreports/ incubation.…”
Section: Human Retinal Explantsmentioning
confidence: 99%
“…These cells have been reported in the mature cadaveric human retina, where they were found predominantly in the retinal periphery ( Mayer et al, 2005 ; Bhatia et al, 2009 ; Too et al, 2017 ) and in the epiretinal membranes of patients with proliferative retinopathies ( Mayer et al, 2003 ; Johnsen et al, 2012 ). Recently, we identified retinal progenitor cells of MG lineage in surgical retinal explants excised from the mid-periphery of living donors undergoing rhegmatogenous retinal detachment repair ( Too et al, 2021 ). Together, these cells serve as a potentially important homologous – or autologous (if derived from living donors) – source of stem/progenitor cells that warrant further investigation of their potential in regenerative medicine.…”
Section: Functions Of Müller Glia In the Retinamentioning
confidence: 99%
“…Subsequent studies report that most, but not all, cadaveric or surgical retina could give rise to immortalized proliferation ( Lawrence et al, 2007 ; Giannelli et al, 2011 ), which is perhaps unsurprising given the diversity of genetic makeup and retinal microenvironment amongst human donors, as well as topographical variations in the retinal loci from which samples have been obtained. MG derived both from cadavers ( Lawrence et al, 2007 ) and living donors ( Giannelli et al, 2011 ; Too et al, 2021 ) have been shown to express stem/progenitor-cell protein markers, such as Sox2, Pax6, and Chx10. Furthermore, they can be induced by various cocktails of growth/differentiation factors for differentiation into post-mitotic retinal cells, such as rod- ( Giannelli et al, 2011 ; Jayaram et al, 2014 ) and RGC-precursors ( Singhal et al, 2012 ).…”
Section: Müller Glia For the Treatment Of Retinal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work shows that culturing of human surgical retinal explants obtained from the equatorial retina reveals spontaneously migrating cells that express ESC markers, as Pax6 , Sox2, Nestin and also MGC markers, such as GFAP and glutamine synthetase. This implies that following injury, this area of the retina might provide a source of RPCs, since it generates cells that possess the potential for regeneration, with markers consistent with Müller cell lineage[ 225 ].…”
Section: Sc In Rd: Current Approachesmentioning
confidence: 99%